Rethinking Forest Partnerships and Benefit Sharing : Insights on Factors and Context that Make Collaborative Arrangements Work for Communities and Landowners - World Bank (Washington, DC, 2013)
Forest-sector collaborative arrangements come in many forms. The local partner may be a community, an association, or a set of individual landholders. The outside partner may be a private organization or a government. The interest of the local partner may be production of income from the forest, security of access to land, increased labor or small business opportunities, protection of traditionally valued resources, or other values. The interest of the outside partner may be similarly varied, from securing access to forest products, to obtaining the cooperation of the local community in the partner's resource use, to securing a source of labor, to alleviation of rural poverty, to production of environmental services and management of risks. Establishing arrangements that effectively deliver sustainable forest management and benefit local communities is a challenge because of the range of participants, objectives, and scales of partnerships and benefit-sharing arrangements. This study uses an evidence-based approach to provide insights into developing and maintaining collaborative arrangements in the forest sector. It aims to inform discussions and approaches to forest partnership and benefit-sharing arrangements. It also offers guidance on how to implement key factors that influence contract-based forest partnerships and benefit-sharing arrangements.